Social functions of modern library-information institutions (Problems of library management) - Kazimi, Parviz Firudın Oqlu; Agamirzaev, Orkhan (Technium Social Sciences Journal, 2021)
The emergence of the library as a social phenomenon Objective prerequisites for the emergence of libraries. The need for the accumulation and storage of information. Construction of special facilities for document storage. The emergence of the library profession. The appearance of the reader (user) of the library. The beginning of the functioning of the library and its tasks. The transformation of the role of libraries as human society evolves. Analysis and evaluation of the main tasks of the modern library: information, educational, cultural, etc. The library as an indicator of the level of development and material well-being of society. The role of the library in the informatization of society.